Relationship therapy with same-sex couples - Bigner, Jerry J.; Wetchler, Joseph L. (Haworth Press, 2004)
"Relationship Therapy with Same-Sex Couples provides psychologists, therapists, social workers, and counselors with an overview of the array of treatment issues they may face when working with couples from the GLBT community. This book highlights the experiences of therapists who have encountered concerns particular to GLBT clients - especially those in intimate relationships. This resource covers clinical issues, sex therapy, special situations, and training issues for helping therapists successfully counsel same-sex couples."--BOOK JACKET.